1997
DOI: 10.1172/jci119754
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability in the type II TGF-beta1 receptor gene in atherosclerotic and restenotic vascular cells.

Abstract: Cells proliferating from human atherosclerotic lesions are resistant to the antiproliferative effect of TGF-␤ 1, a key factor in wound repair. DNA from human atherosclerotic and restenotic lesions was used to test the hypothesis that microsatellite instability leads to specific loss of the Type II receptor for TGF-␤ 1 (T ␤ R-II), causing acquired resistance to TGF-␤ 1. High fidelity PCR and restriction analysis was adapted to analyze deletions in an A 10 microsatellite within T ␤ R-II. DNA from lesions, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 40 publications
(33 reference statements)
4
121
0
3
Order By: Relevance
“…5 This hypothesis remains attractive, because somatic mutations in the TGF-␤ signaling pathway are relatively common and may contribute to the pathogenesis of certain tumors 12 and atherosclerosis. 13 In the present study, we demonstrate that BMPR-II mRNA and protein expression is mainly localized to the endothelium in the normal pulmonary circulation, although it is also expressed by myofibroblasts comprising concentric intimal lesions in severe PH. In addition, we report that pulmonary vascular BMPR-II expression is reduced in PPH cases, most markedly in those PPH cases with an underlying mutation in the BMPR2 gene.…”
supporting
confidence: 60%
“…5 This hypothesis remains attractive, because somatic mutations in the TGF-␤ signaling pathway are relatively common and may contribute to the pathogenesis of certain tumors 12 and atherosclerosis. 13 In the present study, we demonstrate that BMPR-II mRNA and protein expression is mainly localized to the endothelium in the normal pulmonary circulation, although it is also expressed by myofibroblasts comprising concentric intimal lesions in severe PH. In addition, we report that pulmonary vascular BMPR-II expression is reduced in PPH cases, most markedly in those PPH cases with an underlying mutation in the BMPR2 gene.…”
supporting
confidence: 60%
“…It is noteworthy that microsatellite sequences were mutated in the atherosclerotic tissues but not in normal vascular tissues from the same patients. The observations indicate that there is a common pattern of microsatellite sequence mutation in atherosclerotic plaque collected from different patients and from experimental animals [113,114].…”
Section: Dna Damagementioning
confidence: 81%
“…In a small fraction of cancers, mainly sporadic human tumors, defective repair of mismatched bases results in an increased mutation rate and consequent widespread microsatellite instability [112]. Mc Caffrey et al [113] found an increased mutation rate of microsatellite sequences in patients with cardiovascular atherosclerotic lesions. The demonstration of microsatellite instability in human atherosclerotic plaques suggests that genomic destabilization, which may also affect other genes, can result in the misregulation of the cells harboring these mutations and may play a pivotal role in atherosclerotic mechanisms.…”
Section: Dna Damagementioning
confidence: 99%
“…Одной из первых соматических мутаций, обнару-женных в ГМК атеросклеротических бляшек коро-нарных и сонных артерий человека, является мутация в полиадениновом тракте гена рецептора трансфор-мирующего ростового фактора β, II типа (TGFBR2) [21]. В связи с тем, что данная мутация выявлена в единичных первичных и рестенотических атеро-склеротических бляшках артерий, полагают, что она не принимает участие в патогенезе заболевания [22,23].…”
Section: российскийunclassified